Randomized phase II study of TX followed by XELOX versus the reverse sequence for chemo-naive patients with metastatic gastric cancer - Zhao, Xiao-Yin; Liu, Xin; Li, Wen-Hua; Qiu, Li-Xin; Huang, Ming-Zhu; Wang, Chen-Chen; Chen, Zhi-Yu; Zhang, Wen; Feng, Wan-Jing; Guo, Wei-Jian; Zhu, Xiaodong (Frontiers in Oncology, 2022)
This research found that the clinical outcomes (PFS, ORR, OS) of the non-platinum-based doublet regimen (docetaxel capecitabine combination) were similar to those of the platinum-based (oxaliplatin capecitabine combination) when used as first line therapy for MGC patients. Background Docetaxel, platinum and fluorouracil are the three most important drugs in the treatment of MGC. This study was to compare clinical outcomes of the docetaxel capecitabine combination and the oxaliplatin capecitabine combination as first-line therapy in MGC patients. Methods In this phase II trial, MGC patients were randomly assigned and treated with either TX (capecitabine 1000 mg/m2/twice daily/1-14 days and docetaxel 60/75 mg/m2 on the 1st day) (because of toxicity, the dose of docetaxel was reduced to 60 mg/m2) or XELOX (capecitabine the same dose with TX and oxaliplatin 130 mg/m2 on the 1st day) as first-line therapy. After progression, patients were crossover to the other group as second-line treatment. Results Total 134 MGC patients were randomized (69 in TX, 65 in XELOX). There was no significant difference between the PFS of the two groups (TX vs XELOX, 4.6 months vs 5.1 months, p=0.359), and the SFS (9.3 months vs 7.5 months, p=0.705), OS (13.1 months vs 9.6 months, p=0.261), and ORR (46.4% vs 46.2%) were also similar. Among patients with ascites, the TX group had significantly longer PFS and OS than the XELOX group. A total of 85 patients (48 in TX, 37 in XELOX) received second-line treatment, with overall survival of second-line chemotherapy (OS2) of 8.0 m and 5.3 m (p=0.046), respectively. Grade 3 to 4 treatment-related adverse events of first line treatment occurred more in TX group than that in XELOX group(60.6% vs 55.4%). Conclusion TX regimen is an alternative choice of first-line treatment for MGC patients. We still need to explore the large number of cohort to confirm this results.